Quantum scattering and semiclassical transition state theory calculations on chemical reactions of polyatomic molecules in reduced dimensions - Greene, SM; Shan, X; Clary, DC (Wiley, 2018)
The reduced‐dimensionality procedures have particular advantages in applications to chemical reactions of polyatomic molecules. They make quantum reactive scattering (QRS) calculations feasible for many new reactions and allow for suitable potential energy surfaces (PESs) to be produced with minimal computational expense. This chapter describes some of the recent computations carried out with this reduced dimensionality approach. By combining semiclassical transition state theory (SCTST) with reduced dimensions (RD) procedures, a particularly computationally inexpensive and powerful approach is obtained for calculating rate constants, which retains the accuracy of multidimensional theory to some extent. The chapter describes this approach, where the accuracy of the semiclassical tunneling procedure is also tested by comparison with the quantum scattering‐reduced dimensionality calculations on the hydrogen abstraction and exchange reactions of a variety of hydrocarbon molecules. The examples chosen here for testing these approaches are reactions of hydrocarbon molecules.